Análise constitutiva do discurso das mães de crianças em tratamento fonoaudiológico sobre a interação com o profissional - Maria de Fatima Garrido Rodrigues (2010)
In daily conversation, people express their opinion using language organized in clauses which represent their knowledge about internal and external world, as an exchange of goods and services or information, to maintain or to construct relationships and representing in semantic sequences of clause complexes a narrative. The aim of this study is to analyse by the Linguistic theories of Systemic Functional Grammar, Social Semiotic and Critical Discourse Analysis, discourse and textual production by mothers of children in speech therapy in an institution which receives patients from public health service and the researcher in an interview about what they think of interaction. We based on a macro-analysis or discursive one and on a micro-analysis or semantic one to identify: a) language functions which construe the experience of world by participants and processes of transitivity system; b) polarity and modality expressed in interpersonal metafunction; c) linguistics resources used in taxes relations and types of logic-semantics relations. These general purposes can be distributed more specifically in others: i) to explain discursive formations and identities in discourses; ii) to characterize the social profile of the participants. The qualitative research was constituted of texts produced by five mothers who have their children in speech therapy. The method used was an audio recorded conversation with them. The quantitative register of mothers social profile had the purpose to know the participants. The results showed mothers as principal participants involved in different mental, verbal, behavioral and material processes. Their role as suppliers of information about their children, expressed by polarity and modality and the speech therapist role as seeker of information demanded, but as supplier too. Mothers discourses revealed their points of view about interaction and the texts were configured in narratives, constructed as a series of episodes related with its importance, purposes and the speech therapy. We concluded that the model of interaction by means of information was sustained. However some important changes were observed to construct more solidarity in this kind of relationship.